Diversity of yeasts and moulds in dairy products from Umbria, central Italy. Issue 2 (14th May 2021) - Cenci-Goga, Beniamino; Cruciani, Deborah; Crotti, Silvia; Karama, Musafiri; Yıldırım, Gamze; Bulut, Menekşe; Marino, Concetta; Grispoldi, Luca
Abstract: In this research communication we report on the diversity of yeast and mould species in 69 samples of milk and different dairy products from three plants located in Umbria, central Italy. Isolates were characterised both macroscopically and microscopically and then identified by PCR and genome sequencing of the ITS region and the D1–D2 domain of the large-subunit rRNA gene for filamentous fungi and yeasts, respectively. Out of the 69 samples analysed, 51 (73.9%) tested positive for the presence of yeasts, whereas moulds were detected in 25 (36.2%) samples. A total of 9 yeast species belonging to 8 different genera and 13 mould species belonging to 6 different genera were isolated. The most common genera isolated were Debaryomyces and Kluyveromyces among the yeasts and Penicillium and Galactomyces among the moulds. Microbiota play a key role in the formation of flavour, aroma, texture and appearance of dairy products. This complex microbial ecosystem includes both cultured and external bacteria, yeasts and moulds. Some of them have an important role in the production of cheeses, whereas others are responsible for dairy product spoilage, resulting in significant food waste and economic losses. Some species can produce mycotoxins, representing a potential hazard for the consumer's safety. This study provides interesting information on the diversity of fungi species in dairy products from central Italy that can be of major importance to identify these products and to develop adequate strategies for fungal spoilage control and consumer safety.